VIRTOURAL: MOBILE APPS AS VIRTUAL TOURISM AND E-MARKETPLACE INTEGRATED WITH VIRTUAL REALITY TO IMPROVE TOURISM AND UMKM IN PACITAN DISTRICT: VIRTOURAL : MOBILE APPS SEBAGAI VIRTUAL TOURISM DAN E-MARKETPLACE TERINSTEGRASI VIRTUAL REALITY GUNA MENINGKATKAN PARIWISATA DAN UMKM KABUPATEN PACITAN - Shihabudin, Ahmad; Nuryana, I Kadek Dwi (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
This research aims to describe the concept design and implementation of Virtoural, which is Mobile Apps as Virtual Tourism and E-Marketplace Integrated Virtual Reality To Improve Tourism and MSMEs in Pacitan Regency. This research uses the R&D method (Research and Development) which consists of four stages, namely stage Define, Design, Develop, and Dissermination. But for developmen tmobile app This only reaches the Develop stage, namely creating a Virtoural prototype. Virtoural is an application as virtual tourism Pacitan Regency ande-marketplace by using the Pacitan Regency tourist destination as its base by integratingVirtual Reality inside it. The features in Virtoural are the start/registration page, main menu, tourist exploration menu, best destination menu, souvenir menu, and user account menu. The stages for designing mobile app Virtoural is the problem identification stage, design stage, assembly stage, trial & evaluation stage, implementation stage, and product evaluation & development stage. In this way the Virtoural application can be implemented well. After this application is implemented, it is hoped that it can help the tourism sector and MSMEs in Pacitan Regency.